Frenotomy in children with ankyloglossia: a scoping review protocol (Research, Society and Development, 2022)
Objective: To map and describe the scientific evidence about the indication of frenotomy in children with ankyloglossia. Method: Scope review protocol, registered in Open Science Framework no. osf.io/efnu4, and conducted following the recommendations of the Joanna Briggs Institute manual, in five stages: (1) identification of research questions; (2) identification of relevant studies; (3) selection of studies; (4) data analysis; and (5) grouping, synthesis and presentation of results, with the guiding question: What is the existing scientific evidence regarding the indication of frenotomy in children with ankyloglossia? The Preferred Reporting Items for Systematic Reviews and Meta-analyses Scoping Review checklist will be used to search for articles in the following databases: PubMed, Lilacs via Virtual Health Library, Scielo, Web of Science, via Higher Education Personnel Improvement Coordination portal and gray literature. For eligible studies that meet all inclusion and exclusion criteria, a data extraction tool to collect and store the main characteristics of the studies will be used and the results will be presented through narrative synthesis and tables and graphs.